CUP STACKING GAMES: THE CONTRIBUTION IN IMPROVING STUDENTS SPEAKING ABILITY - St. hartina; Rabiah; Masruddin (JLE: Journal of Literate of English Education Study Program, 2022)
Cup stacking games allows the equal opportunities to each student to speak up during the classroom. Thus, the present study is to improve the students' speaking ability in by utilizing Cup stacking games. This study applied classroom action research which was conducted in four stages; planning, action, observation, and reflection. A total of 22 students in eleventh grade of SMAN 6 Luwu is the subject of speaking tests and observation.. The results of data analysis showed a significant improvement in students' speaking abilities until the second cycle. speaking test in cycle 2, there are 80 % of students reach 3.1-4.0 score categorized as good. In addition, the observation of cycle 2 showed that there are 75% of students got good criteria in class participation. Both of these criteria indicated that utilizing the cup stacking games can boost the students' speaking ability.